The Influence Of Commitment On Employee Performance Through Organizational Culture At The North Labuhanbatu District Inspectorate - Tiolina Simatupang; Fajar Rezeki Ananda Lubis; Syaifuddin (International Journal of Economics, Business and Innovation Research, 2026)
The declining quality of bureaucracy is largely due to various internal and external factors. Therefore, this study will examine the influence of commitment on employee performance through organizational culture. The study population was all employees and related agencies at the North Labuhanbatu Regency Inspectorate. The research method used is an explanatory quantitative approach. The study will conduct tests using independent variables: Commitment (X), one mediating variable, Organizational Culture (Z), and one dependent variable, Employee Performance (Y). The data collection process involved field observation and a questionnaire. Data analysis used Structural Equation Modeling (SEM). The results of the study indicate a positive influence of employee commitment on employee performance. Furthermore, employee commitment significantly influences organizational culture. Likewise, organizational culture significantly influences employee performance. The results of the indirect variables indicate a significant influence of employee commitment on employee performance with organizational culture at the North Labuhanbatu Regency Inspectorate.